Permeable Pavement Systems: Technical Considerations - Eban Bean; Mark Clark; Barbra C, Larson (EDIS, 2019)
Permeable pavement systems are Green Stormwater Infrastructure practices that can reduce runoff while supporting vehicle and pedestrian traffic. This new 8-page document provides technical details of permeable pavement systems, such as application, system elements, design, installation, operation, maintenance, crediting, and costs, in order to inform planners, engineers, landscape architects, local government officials, and other professionals in the built environment about the considerations for implementing and maintaining permeable pavements. Written by E. Bean, M. Clark, and B. Larson, and published by the UF/IFAS Department of Agricultural and Biological Engineering, April 2019. https://edis.ifas.ufl.edu/ae530